The Internalization of Religious and Cultural Values in Shaping a Young Generation of Character in the Modern Era - Ni Nyoman Rahmawati (IAHN-TP Palangka Raya, 2026)
Globalization and digitalization have triggered rapid and complex social changes, particularly for the younger generation as the group most adaptable to technological advancements. These transformations present not only opportunities but also serious challenges, including identity crises, moral degradation, and cultural disruption. This study aims to analyze the influence of globalization and digitalization on changes in the values and identity of the younger generation, the urgency of internalizing religious and cultural values in character formation, and strategies for their implementation in the modern era. The study employs a qualitative approach using literature review (library research) and descriptive-analytical analysis, grounded in the theory of value internalization and the theory of globalization. The findings indicate that globalization leads to value instability, a shift of local cultures toward the dominance of global culture, and the emergence of generational value gaps. The reinforcement of religious values serves as a moral guide, while cultural values preserve collective identity and social sustainability. Strategies for value internalization are implemented through the synergy of family, education, and society in a sustainable and contextual manner.